Peripheral arterial disease and diabetes mellitus - Coce, Franjo (Array, 2008)
Summary: The aim of this study was to establish clinical characteristics and consequences of peripheral arterial disease in diabetic patients. The study included 350 inpatients, 54.6% men and 45.4% women. Women were statistically significantly older than men (67.2±9.1 vs. 61.7±9.8 years; p<0.0001). There were no statistically significant differences in diabetes duration (15.1±9.4 and 16.0±8.2 years in men and women, respectively; χ2-test=3.2; df=2; NS). Among study patients, 87.2% had lower leg peripheral arterial disease, 27.3% had an isolated form, and 59.9% had changes in proximal arteries. Asymptomatic stage of the disease was found in 12.6%, intermittent claudication in 38.9%, chronic critical ischemia in 25.7%, and foot ulcer or gangrene in 22.8% of patients. A total of 36 bypasses, 20 percutaneous transluminal angioplasties and 10 lumbar sympathectomies were performed in 15.7% of patients. A hundred and seven amputations, 70.1% minor and 29.9% major, were performed in 22.8% of patients. Early detection and regular ultrasound check-ups can increase the number of surgical or endovascular interventions, thus reducing the rate of amputations